2019
DOI: 10.1080/08989621.2019.1621755
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a responsible conduct of research education program at Duke University School of Medicine

Abstract: Academic medical centers rarely require all of their research faculty and staff to participate in educational programs on the responsible conduct of research (RCR). There is also little published evidence of RCR programs addressing high-profile, internal cases of misconduct as a way of promoting deliberation and learning. In the wake of major research misconduct, Duke University School of Medicine (DUSoM) expanded its RCR education activities to include all DUSoM faculty and staff engaged in research. The prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…In the category (Education for IR), most studies value training in integrity-related standards and principles to foster good research practices and prevent research violations. However, some studies (Knysh et al, 2020;Satalkar & Shaw, 2019;Simon et al, 2019) indicate that training programs do not immediately solve IR problems. In 2017, a study was conducted that highlighting the existence of proactive and reactive approaches to integrity and research misconduct (Hyytinen & Löfström, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the category (Education for IR), most studies value training in integrity-related standards and principles to foster good research practices and prevent research violations. However, some studies (Knysh et al, 2020;Satalkar & Shaw, 2019;Simon et al, 2019) indicate that training programs do not immediately solve IR problems. In 2017, a study was conducted that highlighting the existence of proactive and reactive approaches to integrity and research misconduct (Hyytinen & Löfström, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Simon et al, (2019) reported the experience of implementing an educational program from the presence of undue research. For their part (Satalkar & Shaw, 2019) point out that to reduce misconduct, it is necessary to promote personal integrity in schools and, at the same time, continuously train at the university level.…”
Section: Resultsmentioning
confidence: 99%
“…This more recent shift in attention from cases of misconduct to QRPs and the replication crisis has reshaped the definition of RI. Instead of referring negatively to misconduct, it is now used positively to indicate efforts to increase the validity and trustworthiness of research (18,19).…”
Section: What Is Research Integrity?mentioning
confidence: 99%
“…Interviewees expressed that our workshops were: "interactive and colorful, and not boring…" (IN 3), "quite remarkable" (IN 6), "insightful and interesting" and "innovative" (IN 7), "fun" and "rewarding" ( IN 8). One of our interviewees mentioned that when "you have [people] on board [and engaged], they will implement [the guidelines] because they like it and because they contributed to it" (interviewee number, IN 18). Another participant remarked that engaging stakeholders actively is especially necessary to get "buy-in", i.e.…”
Section: Stakeholder Engagementmentioning
confidence: 99%
See 1 more Smart Citation